2003
DOI: 10.1176/appi.ajp.160.7.1350
|View full text |Cite
|
Sign up to set email alerts
|

Five-Year Outcomes Following Psychiatric Consultation to a Tertiary Care Emergency Room

Abstract: These findings reveal relationships between diagnostic profiles and future psychiatric hospitalization and mortality rates. This information could focus psychiatric and medical interventions for high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 9 publications
0
20
0
7
Order By: Relevance
“…23 The rate of referrals to psychiatric hospitalization (8.2%) was lower than reported in other Brazilian studies and internationally. 12,15,18 This finding probably reflects the characteristics of the population, as well as the care network available in the city.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…23 The rate of referrals to psychiatric hospitalization (8.2%) was lower than reported in other Brazilian studies and internationally. 12,15,18 This finding probably reflects the characteristics of the population, as well as the care network available in the city.…”
Section: Discussionmentioning
confidence: 86%
“…This difficulty has also been observed in other studies conducted in emergency services. 18,24,25 This problem limits data gathering, thus resulting in high rates of missing data and hindering descriptive analyses and establishment of correlations.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflected by their high admission rates (22% to 35% 2,8,[13][14][15] ; and up to 54% for patients with substance abuse). 15 This high admission rate, combined with a lack of acute care beds on inpatient psychiatric units 1-3,10,11 results in boarding of admitted patients in ED corridors.…”
mentioning
confidence: 99%
“…This difficulty was also observed in other studies made in emergency services. 9 This problem limits the data collection, resulting in high rates of missing data and hindering the descriptive analyzes and the establishment of correlations.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…8 A prospective study conducted in a tertiary Emergency Room Unit in Canada showed that 59% of patients who had been treated by the psychiatric team were diagnosed with primary or secondary substance dependence. 9 North American data indicate that there is an increasing tendency in emergency admissions at the Emergency Rooms due to PAS related-disorders, being more significant in relation to illicit substances. 10 Patients with PAS use disorders, when compared to patients who seek Emergency Rooms for other reasons, are younger.…”
mentioning
confidence: 99%